Development of Website-Based Interactive Learning Media in Class V Social Sciences Lessons - Zaen Nuraini (Yayasan Insan Mulia Bima, 2024)
Technological advances that continue to develop and teachers' lack of knowledge regarding technological developments are the main causes of weak creation and development of learning media, while the quality of students depends on the quality of a teacher. The aim of this research is to find out the procedures used in developing website-based interactive learning media and to determine the feasibility of the media being developed. The research results show that website media is feasible to implement. The media validation results obtained an average percentage of 80% and the material expert validation results obtained a percentage of 90%. Website-based interactive learning media is able to develop student learning outcomes, where learning outcomes in stages I and II are 95% and 97% respectively. The response from teachers and students was also very enthusiastic in implementing learning media. Based on the research results, website-based learning media is very feasible and can be applied on a larger scale.